The Influence Of Motivation, Communication And Working Environment To Employee Performance At Kelurahan In District Of SukoharjoWith A Commitment As A Moderating Variable - Widayanti, Nunung (-)
The purpose of this study are to examine the influence of motivation, communication and work environment to employee performance with a commitment as a moderating variable at Kelurahan in District of Sukoharjo. Hypothesis that have been formulated in this study were : a significant influence of work motivation, communication and work environment to employees performance with a commitment as a moderating variable.This study is a survey research. The data are primary data collected through questionnaires to 33 employees at Kelurahan in District of Sukoharjo. The data that has been obtained is tested by validity, reliability test, regression analysis, t test, F test and R2 test.t-test results showed that the work environment and commitment have a significant influence on the performance of an employee, but motivation, communication was not a significant positive influence on performance. F-test results showed that the variables of work motivation, communication, work environment and commitment significantly influence the performance of employees simultaneously. Moderation test results show that the commitment can not be used as a moderating variable between work motivation, communication, work environment on employee performance. Test results showed R2 equation 1 for 0,917 or imply that the variability of the dependent variable can be explained by the variability of the independent variable was 91.7% while the remaining 8.3% is explained by other variables that are not included in the regression model as in equation 2 R2 Test results obtained 0,931 means that the variability of the dependent variable that can be explained by the variability of the independent variable was 93.1% while the remaining 6.9% is explained by other variables that are not included in the regression models such as: job satisfaction, work ability. Based on the results of hypothesis test for the first equation without moderating variable, and the second equation with a commitment as moderating variable, it can be concluded that the variables of organizational commitment is not able to moderate the influence of motivation, communication and working environment on the performance due to weaken the influence of motivation, communication and working environment on the performance. Therefore, to improve performance is without moderation organizational commitment. Things are recommended to improve performance without moderation organizational commitment.Keywords : motivation, communication, work environment, commitment, performance.